2012
DOI: 10.1002/fam.2167
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally selective and adaptive surfaces for protection against radiative heating: ITO and VO2

Abstract: SUMMARY Two surface materials for reducing absorptivity of heat radiation from fires have been investigated. The first is VO2, which is a thermochromic material. When the temperature of a VO2 surface increases over a certain temperature, it switches, ideally, from infrared (IR)‐absorbing to IR‐reflecting. VO2 window coatings are still on a research level, yet to be commercialized. In this study, VO2 powder available on the market was investigated. The thermochromic effect could be identified but was not large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Moreover, the absorption coefficient changes with the thickness as shown by Linteris et al [ 21 ] even if this change is small for polyethylene. Finally, the absorption depends on the spectral distribution of the radiation which changes with the temperature of the heat source [ 16 , 21 , 22 , 24 ]. As a result, the absorptivity of the materials should change when heat flux changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absorption coefficient changes with the thickness as shown by Linteris et al [ 21 ] even if this change is small for polyethylene. Finally, the absorption depends on the spectral distribution of the radiation which changes with the temperature of the heat source [ 16 , 21 , 22 , 24 ]. As a result, the absorptivity of the materials should change when heat flux changes.…”
Section: Resultsmentioning
confidence: 99%
“…Försth et al, have developed a thin coating based on indium tin oxide. This coating reduces the absorptivity of PMMA from 0.93–0.96 to 0.58–0.73 depending to the heat source and the type of PMMA [ 16 ]. The TTI in a cone calorimeter test at 25 kW/m 2 is significantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising TCOs is indium tin oxide (ITO), which combines high transparency and conductivity. ITO is widely used for fabrication of transparent electrodes of liquid crystal screens [2], organic light emitting diodes (OLEDs) [3], touch screens and solar cells [4], as well as for heat [5] and electrostatic protection [6]. One of the mostly exploited ITO structures possesses the form of thin film, which can be fabricated via several techniques, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that applying a low-emissivity coating (Cr/Cu/SiO 2 ) less than 1 μm thick increased the TTI of PC and PA6.6 substrates by several orders of magnitude in MLC testing and considerably reduced their flammability indexes . Experiments on transparent conductive oxides on PMMA and thermochromic materials on steel and glass , were then reported but without reaching the low emissivity obtained with copper. Sonnier et al have proposed polyethylene composite coatings filled with aluminum flakes; however, in their case, the top layer was thicker (from 65 to 100 μm), which might not be necessary to reach low emissivity and may limit its impact by introducing more flammable material .…”
Section: Introductionmentioning
confidence: 99%